Self-evaluated ethical competence of a practicing physiotherapist: a national study in Finland - Kati Kulju; Riitta Suhonen; Pauli Puukka; Anna Tolvanen; Helena Leino-Kilpi (BMC, 2022)
Background Patients have the right to equal, respectful treatment. Nowadays, one third of patient complaints concern health care staff's behavior towards patients. Ethically safe care requires ethical competence, which has been addressed as a core competence in physiotherapy. It has been defined in terms of character strength, ethical awareness, moral judgment skills in decision-making, and willingness to do good. The purpose of this study was to analyze the ethical competence of practicing physiotherapists. Method A self-evaluation instrument (Physiotherapist's Ethical Competence Evaluation Tool) based on an analysis of a concept "ethical competence" was constructed in 2016 and physiotherapists (n = 839), working in public health services or private practice responded to the questionnaire. Results Based on the results, most of the physiotherapists evaluated themselves highly ethically competent in all areas of ethical competence, subscales being Strength, Awareness, Skills and Will. Willingness to do good was evaluated as highest, while character strength, including the strength to support ethical processes and speak on behalf of the patient, was evaluated the lowest. Physiotherapists most commonly consult a colleague when encountering an ethical problem. Other methods for problem solving are not very familiar, neither are the international or national ethical codes of conduct. Conclusions This was the first attempt to assess all aspects of ethical competence empirically in a clinical environment in physiotherapy, using a novel self-evaluation instrument. Even if physiotherapists evaluate themselves as competent in ethics, further exploration is needed for ethical awareness. Also the patients' viewpoints about ethically competent care should be considered, to better ensure ethical safety of the patient.